Prediabetes and CKD: does a causal relationship exist? (2024)
The relationship between diabetes and the development of kidney complications is well known, but the understanding of prediabetes and insulin resistance with impaired kidney function has been scarcely assessed. Various factors could explain this phenomenon, from the lack of standardization in the definitions of prediabetes, to the erratic and inconsistent evidence in large-scale epidemiological and cohort studies. It seems that the pathophysiological pathway of prediabetes could be related to inflammation and neurohormonal hyperactivation, factors present even before the onset of diabetes, which might be the main drivers of glomerular hyperfiltration, albuminuria, and impaired glomerular filtration rate. It is possible that existing treatments for the management of diabetes, as metformin or SGLT2 inhibitors may also be useful in patients with prediabetes with evidence of functional and structural kidney damage. The purpose of this review is to summarize the evidence regarding the relationship between prediabetes(preDM) and the development of CKD.